Implementing pedagogical content knowledge in teaching and learning entrepreneurship at Community College: an instructional enrichment approach - Sipon, Merhayati; Lope Pihie, Zaidatol Akmaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
Teachers plays an important role in class, not only to teach, but they also plays the role of model (in their subject matter) to the audience (students). A good teacher is such like an actor on the stage, the more they were in control and knowledgeable of the topic or subject of the play, the more easier the audience can understand the action of play. Sometimes it will be able to induce the audience to stand up voluntarily giving tribute and a big applause. To get an impression of this effective, teachers need to be skilled and knowledgeable in their own field. These kind of effect are try to be conveyed in the teaching and learning of entrepreneurship subject at Community Colleges. This concept paper embarks on the discussion of implementing pedagogical content knowledge (PCK) in Entrepreneurship Education (EE) at Community College. Many empirical studies confirmed that PCK will improve students understanding and encourage students critical thinking. This study also highlight the effects of PCK in producing a high quality of teaching and learning especially in EE. The implications for future research on the effects of PCK was also discussed.